Substandard linguistic items in Russian canned jokes - E. Ia. Shmeleva; A. D. Shmelev (Шаги)
This article analyzes Russian canned jokes with substandard linguistic items. Two types of such jokes are distinguished: (1) jokes where obscene words serve the point and (2) jokes where obscene words increase the humorous effect. The article gives an account of the role that substandard items play in creating the «linguistic masks» of certain joke characters, which correlate with their «behavior masks». It discusses various types of such texts: jokes about foreigners, ethnic jokes, jokes about Armenian radio, political jokes, jokes about family life, etc. Substandard lexical units, that is, obscene or vulgar words, may be found in all of the above-mentioned jokes. The article describes the role of substandard language in creating «linguistic masks» of joke characters and the correlation of these linguistic masks with their «behavior masks». In particular, it mentions the linguistic masks and behavior masks of Chapaev, Vovochka, and Lieutenant Rzhevsky. Each of these characters has their own linguistic and behavior masks. In particular, Chapaev is an uneducated communist military commander of the Russian Civil war era who uses obscene words only when he is severely irritated; Vovochka is a schoolboy who reminds «dirty Johnny» of American jokes; Lieutenant Rzhevsky combines the characteristics of a nobleman and a rude soldier.